KOHERENSI KEBIJAKAN KETAHANAN KELUARGA DAN TUMPANG TINDIH MANDAT PENYELENGGARAAN PENDIDIKAN PRA NIKAH DI INDONESIA - Gazi Gazi; Iif Fikriyati Ihsani; Wira Kurnia (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2022)
This paper explores the actualization of the policy of providing premarital education in Indonesia, which in this case is elaborated through 3 Ministries of Municipal Religion, namely the Ministry of Religion of Yogyakarta City, Depok City and Cirebon City. The research is based on the hypothesis that the Ministry of Religious Affairs is tasked with providing premarital insights through premarital education to build a happy and healthy marriage. The Ministry of Religious Affairs itself has issued regulations for pre-marital education from 1961 to 2017 through the idea of the Sakinah Family Movement which continues until now. Using a descriptive analytical approach, researchers interviewed stakeholders who are authorized for the implementation of pre-marital education and observed activity instruments to get a detailed picture of the actualization of pre-marital education policies in 3 research areas. Researchers also explored the area of authority in the scope of premarital education regulations from 1961 to 2017 and their impact on the implementation of pre-marital education. Researchers found that the regulation of premarital education is legally independent and does not have the continuity of the program between each other. As a program overshadowed by regulation for the past nearly 5 years and financed by public funding, premarital education is still not a measurable program, either to look at its effectiveness into the function of family resilience and or into the function of political partisanship. The regulation of premarital education is still only part of the fulfillment of the administration of budgeting and financing. As a result, in each research area, the interpretation of policy implementation is not the same and cannot be evaluated to see the success rate. Through a period of implementation for approximately 5 years, regulations on premarital education need to be evaluated and restructured comprehensively.